A Rare Presentation of Renal Papillary Necrosis in a COVID-19-Positive Patient. (13th January 2021) - Tallai, Bela; Gulistan, Tawiz Gul; Alrayashi, Maged Nasser Aa B.; Al Mughalles, Salah Abdulhabeb Abdulwali; Kamkoum, Hatem Mostari; Ebrahim, Mohamed Ali A.; Abdelkarim, Mohamed Abdelkarim Ali; Salah, Morshed Ali
Abstract : In this case report we describe an unusual presentation of severe acute papillary necrosis in a COVID-19-positive patient. An emergency flexible ureteroscopy greatly helped in the establishment of the diagnosis. In the international literature, there is a paucity of intraoperative endoscopic images representing severe renal papillary necrosis. We present a case of severe acute renal papillary necrosis in a 49-year-old south-Asian, COVID-19-positive male patient who needed emergency urological intervention for macroscopic hematuria and urinary retention due to clot formation in the urinary bladder. The patient underwent emergency cystoscopy, clot evacuation, and by rigid and flexible ureteroscopy. The diagnosis was only confirmed in the postoperative period, retrospectively. Finally, the patient fully recovered due to the multidisciplinary management. Diagnosis of rare clinical entities can be sometimes challenging in the everyday routine practice. Having atypical clinical course, the surgeon should be prepared and sometimes must take responsible decisions promptly, even if needed intraoperatively, to manage unexpected findings in order to get the right diagnosis without compromising the patient's safety.